2007
DOI: 10.1590/s1516-635x2007000200007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of energy intake on performance and carcass composition of broiler chickens from two different genetic groups

Abstract: In order to evaluate the effect of energy intake and broiler genotype on performance, carcass yield, and fat deposition, 600 one-day-old male chicks from two different genetic groups (AgRoss 308 -commercial line and PCLC -Embrapa non-improved line) were fed diets with different metabolizable energy level (2950, 3200 and 3450 kcal/kg). A completely randomized experimental design in a 2X3 factorial arrangement with four replications of 25 birds per treatment was applied. In order to ensure different energy intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
29
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 12 publications
8
29
1
1
Order By: Relevance
“…The superior performance of Ross 308 than Hubbard in 21-day weigh and weight gain during the restriction period has been reported in similar studies by Bruggman et al (2005), Rosa et al (2007). Plavnik and Balnave (1992) and Dozier et al (2003), however, restricted the feed intake of different strains of broilers for 7 and 5 days respectively during the starter period and reported insignificant differences among strains in response to feed restriction.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The superior performance of Ross 308 than Hubbard in 21-day weigh and weight gain during the restriction period has been reported in similar studies by Bruggman et al (2005), Rosa et al (2007). Plavnik and Balnave (1992) and Dozier et al (2003), however, restricted the feed intake of different strains of broilers for 7 and 5 days respectively during the starter period and reported insignificant differences among strains in response to feed restriction.…”
Section: Discussionsupporting
confidence: 72%
“…Benyi et al (2011) reported significant strain × feeding regime interactions effects on 35-day weight, weight gain and feed intake. The significant differences between the strains in feed intake, growth rate and market weight during the entire study period have been previously reported (Rosa et al, 2007) but other authors such as Dozier et al (2003) reported insignificant differences among strains of broilers in response to skip-a-day feed restriction. The similar feed utilization of Ross 308 and Hubbard observed in this study supports similar reports by Dozier et al (2003) and Khajali et al (2007) but is contrary to an observation by Ghazanfari et al (2010) that skip-a-day feed restriction improved feed efficiency.…”
Section: Discussionsupporting
confidence: 56%
“…However, the level of fat pad of the native chicken breeds was again much lower than of exotic broiler chicken (Azizi et al 2011). The absence of effect on dressing percentage and cut carcass composition associated with the similar protein energy ratio among all treatment diets, Rosa et al (2007) said that some of the results of the experiment showed that the content of energy and protein in the diet had no influence on the composition of cut carcass composition of chicken.…”
Section: Carcassmentioning
confidence: 88%
“…However, the present findings and those of Kamran et al (2004), and Ardekani and Chamani (2012) showed no significant difference in liver weight of control and low DPL fed birds. Variations in strain, dietary energy levels (Rosa et al, 2007), and age (Bowes and Julian, 1988) may have contributed to the discrepancies. The greater relative heart weights of birds fed 16.2% DPL could be explained by their lower body weights compared to other groups.…”
Section: Amino Acids Profile For Tropical Climatementioning
confidence: 99%